Phase change materials, phase change memory chips, memory devices, and electronic devices

JP2026533894APending Publication Date: 2026-10-13HUAWEI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026519075
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-03-19
Filing Date
2024-09-25
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

【0007】 本開示のこの実施形態で提供される相変化材料では、元素HfがドープされたGe-Sb-Te相変化ベース材料に、さらに、元素N、元素C、元素In、および元素Gaの少なくとも1つがドープされ、相変化材料層の接着力が高められ、相変化材料層は、別の隣接する機能層と密接に組み合わされ、界面剥離の可能性が低減し、相変化記憶チップの製品歩留りが向上し、生産ラインおよび生産設備への汚染および干渉が回避できる。特に、元素Hfのドーピング量は、1.5%から6.5%であり、元素N、元素C、元素In、および元素Gaの少なくとも1つのドーピング量は、1.0%から5.0%である。これにより、相変化材料層の接着力が改善され、相変化部材が大きな読み取りウィンドウを有し、長寿命を有することが助長される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026533894000001_ABST
    Figure 2026533894000001_ABST
Patent Text Reader

Abstract

This disclosure relates to phase change materials, phase change memory chips, memory devices, and electronic devices, and belongs to the semiconductor memory technology field. The phase change material comprises a Ge-Sb-Te phase change base material and a first doping element and a second doping element doped into the Ge-Sb-Te phase change base material. The first doping element includes the element Hf, and the atomic percentage of the first doping element is from 1.5% to 6.5%. The second doping element includes at least one of the elements N, C, In, and Ga, and the atomic percentage of the second doping element is from 1.0% to 5%. The phase change material has high adhesion and can provide the phase change member with a wide read window, long lifespan, and other properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Chinese Patent Application No. 202311290353.5 entitled "Phase Change Memory" filed on September 28, 2023, and Chinese Patent Application No. 202410316618.2 entitled "Phase Change Material, Phase Change Memory Chip, Memory Device, and Electronic Apparatus" filed on March 19, 2024, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to the field of semiconductor memory technologies, and in particular, to a phase change material, a phase change memory chip, a memory device, and an electronic apparatus.

Background Art

[0003] Phase change memory (PCM) has advantages such as low latency and long fatigue life, and uses a phase change material as a storage medium. The phase change material exhibits low resistivity in a crystalline state and high resistivity in an amorphous state. The phase change memory performs data storage and program / erase based on the resistance difference between the crystalline state and the amorphous state of the phase change material.

Summary of the Invention

Problems to be Solved by the Invention

[0004] In the prior art, a phase change memory includes a plurality of phase change memory units, and the phase change memory unit includes a phase change material layer and barrier layers arranged on both sides of the phase change material layer. Such a sandwich structure including the phase change material layer and the barrier layers is subjected to large stress in process procedures such as annealing and etching. As a result, interfacial delamination may occur between the phase change material layer and another functional layer such as the barrier layer. Consequently, the phase change memory unit where the delamination region is located cannot be used properly, and material particles falling off due to delamination also adversely affect the device and the like.

[0005] In phase-change memory, it is necessary to improve the interfacial adhesion between the phase-change material layer and another functional layer. [Means for solving the problem]

[0006] In one embodiment, a phase change material is provided. The phase change material comprises a Ge-Sb-Te phase change base material and a first doping element and a second doping element doped into the Ge-Sb-Te phase change base material, wherein the first doping element comprises the element Hf, and the atomic percentage of the first doping element in the phase change material is 1.5% to 6.5%, and the second doping element comprises at least one of the elements N, C, In, and Ga, and the atomic percentage of the second doping element in the phase change material is 1.0% to 5%.

[0007] In the phase change material provided in this embodiment of the present disclosure, a Ge-Sb-Te phase change base material doped with element Hf is further doped with at least one of elements N, C, In, and Ga, thereby increasing the adhesion of the phase change material layer, which is closely combined with other adjacent functional layers, reducing the possibility of interfacial delamination, improving the product yield of the phase change memory chip, and avoiding contamination and interference to the production line and production equipment. In particular, the doping amount of element Hf is from 1.5% to 6.5%, and the doping amount of at least one of elements N, C, In, and Ga is from 1.0% to 5.0%. This improves the adhesion of the phase change material layer, which helps the phase change member have a large read window and a long lifespan.

[0008] In some contemplated embodiments, the phase change material further comprises a third doping element, and the third doping element includes at least one of element O, element Si, element B, element Sn, element Bi, element Cd, element Pb, element Zr, element Zn, element Cr, element Al, element Sc, element Y, element Ta, element Ti, element Er, element Lu, element Ho, element Tm, element Dy, element Tb, element Ca, element Nd, element Pr, element Yb, element Ca, and element Ce. Further, the purpose of optimizing the comprehensive performance of the phase change memory member can be achieved by further introducing a specific amount of the third doping element into the phase change material.

[0009] In some contemplated embodiments, the chemical formula of the Ge-Sb-Te phase change base material is (GeTe 1-a ) x (Sb2Te 3-b ) 1-x where x is an atomic percentage, 0<x<1, a and b are parameters related to the atomic weight ratio, 0<a≦1, 0<b≦3, and a=1 and b=1 cannot coexist, or (GeTe 1-c ) x (Sb y Te 1-d ) 1-x where x is an atomic percentage, 0<x<1, y, c, and d are parameters related to the atomic weight ratio, y≧2, 0<c≦1, 0<d≦1, and c=1 and d=1 are not compatible.

[0010] The chemical formula of the Ge-Sb-Te phase change base material is as described above, and in this case, the adhesive force of the phase change material layer can be reliably made higher than the adhesive force of the phase change material layer corresponding to the Ge-Sb-Te phase change base material.

[0011] In another embodiment, a phase-change material is provided, comprising a Ge-Sb-Te phase-change base material and a first doping element and a second doping element doped into the Ge-Sb-Te phase-change base material, wherein the first doping element comprises the element Hf, the atomic percentage of the first doping element in the phase-change material is 1.5% to 7%, and the second doping element comprises at least one of the elements N, C, In, and Ga, the atomic percentage of the second doping element in the phase-change material is 1.0% to 7%, and the sum of the atomic percentages of the first doping element and the second doping element is greater than 4% and less than 10%.

[0012] In this type of phase change material of the present disclosure, the Ge-Sb-Te phase change base material doped with element Hf is further doped with at least one of elements N, C, In, and Ga, thereby increasing the adhesion of the phase change material layer. The phase change material layer is closely combined with another adjacent functional layer, reducing the possibility of interfacial delamination, improving the product yield of the phase change memory chip, and avoiding contamination and interference to the production line and production equipment. In particular, the doping amount of element Hf is 1.5% to 7%, and the doping amount of at least one of elements N, C, In, and Ga is 1.0% to 7%, with the sum of the atomic percent of the two doping elements being more than 4% but less than 10%. This improves the adhesion of the phase change material layer, which helps the phase change member have a large read window, long life, and cycle stability.

[0013] In several contemplated embodiments, the phase change material further includes a third doping element, and the third doping element includes at least one of element O, element Si, element B, element Sn, element Bi, element Cd, element Pb, element Zr, element Zn, element Cr, element Al, element Sc, element Y, element Ta, element Ti, element Er, element Lu, element Ho, element Tm, element Dy, element Tb, element Ca, element Nd, element Pr, element Yb, element Ca, and element Ce. Further, the purpose of optimizing the comprehensive performance of the phase change memory member can be achieved by introducing a specific amount of the third doping element into the phase change material.

[0014] In several contemplated embodiments, the chemical formula of the Ge-Sb-Te phase change base material is (GeTe 1-a ) x (Sb2Te 3-b ) 1-x where x is an atomic percentage, 0<x<1, a and b are parameters related to atomic weight ratios, 0<a≦1, 0<b≦3, and a=1 and b=3 do not coexist, or (GeTe 1-c ) x (Sb y Te 1-d ) 1-x where x is an atomic percentage, 0<x<1, y, c, and d are parameters related to atomic weight ratios, y≧2, 0<c≦1, 0<d≦1, and c=1 and d=1 are not compatible.

[0015] The chemical formula of the Ge-Sb-Te phase change base material is as described above, and in this case, the adhesive force of the phase change material layer can be reliably made higher than the adhesive force of the phase change material layer corresponding to the Ge-Sb-Te phase change base material.

[0016] Further, the chemical formula of the Ge-Sb-Te phase change base material is (GeTe 1-a ) x (Sb2Te 3-b ) 1-x And here, 0.2 <x≦0.4であり、または (GeTe 1-c ) x (Sb y Te 1-d ) 1-x And here, 0.2 <x≦0.4である。

[0017] In this embodiment of the present disclosure, the chemical formula defining the Ge-Sb-Te phase-change base material is as described above, in which case it is possible to ensure that the phase-change member has both low delay and long life, and furthermore, that the phase-change material layer has high adhesive strength.

[0018] In yet another embodiment, a phase-change memory chip is provided. The phase-change memory chip has a plurality of phase-change memory units, each of which has a phase-change material layer, the phase-change material layer being prepared using one of the aforementioned phase-change materials.

[0019] A phase-change memory chip provided in this embodiment of the present disclosure is prepared based on a phase-change material layer of a phase-change memory chip provided in this embodiment of the present disclosure, and the phase-change memory chip has all the advantages of the phase-change material provided in this embodiment of the present disclosure.

[0020] In some hypothetical embodiments, the phase change memory unit further comprises an adhesive layer, which is arranged in a laminated configuration on at least one surface of the phase change material layer. The adhesive layer is configured to enhance the adhesive strength between the phase change material layer and the adjacent functional layer.

[0021] In the phase-change memory chip provided in this embodiment of the present disclosure, not only is the phase-change material improved, but the structure of the phase-change memory chip is also improved, an adhesive layer is added to the phase-change memory chip, the adhesion between the phase-change material layer and the adjacent functional layer is further improved, the possibility of interfacial delamination is greatly reduced, product yield of the phase-change memory unit is improved, and contamination and interference to the production line are avoided.

[0022] In some hypothetical embodiments, the adhesive layer material used in the adhesive layer includes at least one nitride of the target element and a carbide of the target element.

[0023] The target element is selected from at least one of the following elements: W, Ti, Ge, Ta, Hf, In, Ga, Al, Cu, Co, and Mo.

[0024] In some hypothetical embodiments, the adhesive layer material used in the adhesive layer includes a Ge-Sb-Te phase change material doped with a fourth doping element, and the adhesive layer material is different from the phase change material.

[0025] The fourth doping element is selected from at least one of the elements Hf, N, C, In, and Ga, and the atomic percentage of the fourth doping element in the adhesive layer material is 0.01 to 20%.

[0026] In some hypothetical embodiments, the phase change memory unit further comprises a barrier layer, the adhesive layer being positioned between the phase change material layer and the barrier layer and configured to enhance the adhesion between the phase change material layer and the barrier layer.

[0027] In some hypothetical embodiments, the barrier layer material used in the barrier layer includes at least one single-element material, nitride, and carbide of the elements W, Ti, Ge, Ta, Hf, In, Ga, Al, Cu, Co, and Mo.

[0028] In some hypothetical embodiments, the phase-change memory unit further has an electrode layer, The adhesive layer is disposed between the phase change material layer and the electrode layer and is configured to increase the adhesive strength between the phase change material layer and the electrode layer.

[0029] In some hypothetical embodiments, the phase-change memory chip further comprises a plurality of selector units, the selector units and the phase-change memory unit arranged in series.

[0030] In some hypothetical embodiments, the selector unit has a selector layer, and the selector material used for the selector layer has at least one of the S-series selector material, the Se-series selector material, and the Te-series selector material.

[0031] In some hypothetical embodiments, the selector material further comprises a fifth doping element, the fifth doping element being selected from at least one of the following: element B, element Al, element Ga, element In, element C, element Si, element Ge, element Sn, element N, element P, element As, element Sb, element Bi, element O, element Au, element Hf, element Pd, element Cu, element Co, element Ag, element Pt, element Sc, element Ti, and element Ta.

[0032] In yet another embodiment, a storage device is provided by an embodiment of the present disclosure. The storage device comprises a controller and at least one of the aforementioned phase-change storage chips, wherein the controller is configured to store data in the phase-change storage chip.

[0033] The storage device (also called memory) may be configured to store various types of data. This data may include contact data, phone book data, messages, photos, videos, or even instruction data.

[0034] In yet another aspect, an electronic device is provided by an embodiment of the present disclosure. The electronic device comprises a processor and the aforementioned storage device, wherein the processor is configured to store data generated by the electronic device in the storage device.

[0035] The electronic devices in question include, but are not limited to, computers, mobile phones, music players, digital broadcasting equipment, message transmission and reception devices, game control devices, medical devices, fitness equipment, and personal digital assistants. [Brief explanation of the drawing]

[0036] [Figure 1] This figure illustrates the process of interfacial delamination between the phase change material layer and the barrier layer in conventional technology. [Figure 2] This is a diagram showing the mean square displacement of element Hf in a Ge-Sb-Te phase-transition-based material. [Figure 3] This is a diagram showing the mean square displacement of element In in a Ge-Sb-Te phase-transition-based material. [Figure 4] This is a diagram showing the mean square displacement of element Ga in a Ge-Sb-Te phase-transition-based material. [Figure 5] This is a structural diagram of an example of a phase-change memory unit according to one embodiment of the present disclosure. [Figure 6] This is a diagram showing the structure of another embodiment of a phase-change memory unit according to one embodiment of the present disclosure. [Figure 7] This is a diagram showing the structure of yet another example of a phase-change memory unit according to one embodiment of the present disclosure. [Figure 8] This is a diagram showing the structure of yet another example of a phase-change memory unit according to one embodiment of the present disclosure. [Figure 9] This is a structural diagram of an example of a phase-change memory chip according to one embodiment of the present disclosure. [Figure 10] This is a diagram showing the structure of another example of a phase-change memory chip according to one embodiment of the present disclosure. [Figure 11] This is a diagram showing the structure of yet another example of a phase-change memory chip according to one embodiment of the present disclosure. [Figure 12] This is a diagram showing the structure of yet another example of a phase-change memory chip according to one embodiment of the present disclosure. [Figure 13] This is an array diagram of an example of a phase-change memory chip according to one embodiment of the present disclosure. [Figure 14]This is a diagram showing the first preparation step of a phase-change memory chip according to Embodiment 1. [Figure 15] This is a diagram showing the second preparation step of the phase-change memory chip according to Embodiment 1. [Figure 16] This is a diagram showing the third preparation step of the phase-change memory chip according to Embodiment 1. [Figure 17] This is a diagram showing the fourth preparation step of the phase-change memory chip according to Embodiment 1. [Figure 18] This is a diagram showing the fifth preparation step of the phase-change memory chip according to Embodiment 1. [Figure 19] This is a diagram showing the sixth preparation step of the phase change memory chip according to Embodiment 1. [Figure 20] This is a diagram showing the seventh preparation step of the phase-change memory chip according to Embodiment 1. [Figure 21] This is a diagram showing the eighth preparation step of the phase change memory chip according to Embodiment 1. [Figure 22] This is a diagram showing the ninth preparation step of the phase-change memory chip according to Embodiment 1. [Figure 23] This is a diagram showing the tenth preparation step of the phase-change memory chip according to Embodiment 1. [Figure 24] This figure shows the relationship between the lifespan and resistance of a phase-change memory chip in the SET state according to an embodiment of the present disclosure. [Modes for carrying out the invention]

[0037] In the description of embodiments of this disclosure, terms such as “vertical,” “horizontal,” “top,” “bottom,” “up,” and “down” refer to orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are intended merely to facilitate the description and simplified representation of embodiments of this disclosure, and do not indicate or imply that any particular device or element must be constructed and operated in a particular orientation and in a particular position. Accordingly, the terms should not be understood as limiting embodiments of this disclosure. Orientations may change when the product is placed in a different orientation, and for example, “top” and “bottom” may be interchangeable.

[0038] Phase-change memory (PCM), also known as a phase-change memory chip, is a solid-state semiconductor non-volatile memory that uses a phase-change material as its storage medium. The phase-change material can reversibly convert between a crystalline state and an amorphous state. Phase-change memory stores data "0" and "1" by utilizing the difference between the high and low resistivity of the phase-change material in the amorphous and crystalline states.

[0039] The operation procedure for phase-change memory includes an erase (SET) procedure and a write (RESET) procedure. The SET procedure means that a broad, weak electrical pulse is applied to heat the phase-change material, raising its temperature to a temperature between the crystallization temperature and the melting temperature, causing the phase-change material to crystallize in an ordered state, forming a low-resistivity crystalline state, and storing the data "0". The RESET procedure means that a narrow, strong electrical pulse is applied to heat the phase-change material, raising its temperature to a temperature above the melting temperature, causing the phase-change material to melt in an irregular state. After a subsequent rapid cooling quench procedure, the phase-change material moves directly from the molten state to a high-resistivity amorphous state, and the data "1" is stored.

[0040] In the prior art, phase-change memory includes multiple phase-change memory units. As shown in Figure 1, a phase-change memory unit includes a phase-change material layer 100 and barrier layers 300 positioned on both sides of the phase-change material layer 100. In the procedure for preparing phase-change memory, such a sandwich structure including the phase-change material layer 100 and the barrier layers 300 is subjected to many processes such as annealing, graphics, etching, and protective layer coating, and is subjected to significant stress. Consequently, interfacial delamination can occur between the phase-change material layer 100 and another functional layer such as the barrier layer 300 (see Figure 1). As a result, a phase-change memory unit in which a delamination region is located is normally unusable (for example, interfacial delamination occurs between the phase-change material layer and the barrier layer, preventing the phase-change material layer and the barrier layer from bonding), and the particulate material that falls due to delamination also adversely affects the production equipment (e.g., contamination of the production line, interference with the normal operation of the equipment). It is clear that there is a need to improve the interfacial adhesion between the phase-change material layer and the other functional layer.

[0041] In a first embodiment of the present disclosure, a phase-change material is provided. The phase-change material comprises a Ge-Sb-Te phase-change base material and a first doping element and a second doping element doped into the Ge-Sb-Te phase-change base material. The first doping element comprises the element Hf, and the atomic percentage of the first doping element in the phase-change material is from 1.5% to 6.5%. The second doping element comprises at least one of the elements N, C, In, and Ga, and the atomic percentage of the second doping element in the phase-change material is from 1.0% to 5.0%.

[0042] For example, some examples of atomic percentages of the first doping element Hf in phase change materials, though not limited to these, include 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, and 3. This includes 5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, etc.

[0043] For example, some examples of atomic percentages of the second doping element in phase change materials, but not limited to, include 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, etc.

[0044] The second doping element may be one of the elements N, C, In, and Ga. For example, the second doping element may be N, C, In, or Ga, or it may be any combination of any two or any three of the elements N, C, In, and Ga, or it may contain all four elements.

[0045] In the phase-change material provided in this embodiment of the present disclosure, the Ge-Sb-Te phase-change base material is doped with the element Hf and at least one of the elements N, C, In, and Ga, thereby improving the adhesion between the phase-change material layer and another functional layer. The principle of improving the adhesion between the phase-change material layer and another functional layer will be described separately below.

[0046] (1) When the second doping element is element N or element C, element N or element C can bond with element Hf, and an HfN compound or HfC compound is introduced into the phase change material. The lattice constant of the HfN compound or HfC compound does not match the lattice constant of the Ge-Sb-Te phase change base material (for example, the lattice constant of the HfN compound is 0.452 nm, and the lattice constant of the HfC compound is 0.463 nm, which do not match the lattice constant of the Ge-Sb-Te phase change base material (for example, the lattice constant of Ge1Sb4Te6 is 0.612 nm)). Thus, additional grain boundaries are introduced, the particle size of the phase change material is reduced, the roughness of the phase change material is reduced, the contact area and adhesion between the phase change material layer and the other functional layer are increased, and the adhesion of the phase change material layer is enhanced.

[0047] Furthermore, research has shown that when the atomic percentage of element N or element C is between 1.0% and 5.0%, the phase change member can be made to have a larger read window. The principle related to this is as follows: In the operation of a 1S1R type phase change memory chip, the threshold voltage for opening the selector unit and the crystalline phase change memory unit is VtS, the threshold voltage for opening the selector unit and the amorphous phase change memory unit is VtR, and the read window is VtR-VtS. It can be seen that the size of the read window is directly proportional to the difference between the high and low resistances of the phase change material layer.

[0048] On the other hand, HfN and HfC compounds can improve the high resistance of phase transition materials. This helps to increase the read window of the phase transition member. However, if Hf is doped separately into the Ge-Sb-Te phase transition base material, Hf comes into contact with O or another substance with oxidizing properties during the process preparation procedure, so Hf is easily oxidized to form HfOx, but the resistivity of HfOx is greater than the resistivity of the phase transition material. Thus, the low resistance of the phase transition material is increased to some extent, and as a result, the read window of the phase transition member is reduced. However, the melting points of HfN and HfC compounds are 3310°C and 3900°C, respectively, and they have high chemical stability and do not readily react with other elements such as O, so the oxidizability of element Hf is reduced, ensuring that the phase transition member has a large read window.

[0049] However, the effect of element N or element C on the reading window of the phase change member depends on the amount of doping of element N or element C in the phase change material. In this embodiment of the present disclosure, by using relevant experiments, it has been shown that the reading window of the phase change member deteriorates when the atomic percentage of element Hf exceeds 6.5% (outside the limited range of 1.5% to 6.5%) and the atomic percentage of element N or element C exceeds 5.0% (outside the limited range of 1% to 5%).

[0050] For example, the aforementioned "related experiments" are shown as follows:

[0051] Embodiments of this disclosure provide a phase-change material of such a type. Here, the Ge-Sb-Te phase-change base material of the phase-change material is doped with the elements Hf and N, and the ratio of the atomic percentages of the elements in the chemical formula of the Ge-Sb-Te phase-change base material satisfies Ge:Sb:Te=1:4:6 (this may be succinctly referred to as Ge1Sb4Te6, GeSbTe146, or GST146). While other parameters are quantitatively maintained, the low resistance corresponding to the crystalline state of the phase-change material layer and the high resistance corresponding to the amorphous state of the phase-change material layer are evaluated separately by varying the doping amounts of the elements Hf and N. See Table 1 for relevant test parameters and test results.

[0052] [Table 1]

[0053] Table 1 shows that doping the Ge-Sb-Te phase-change base material, which is already doped with element Hf, with element N improves the resistance of the phase-change material layer and thus improves the reading window size.

[0054] Referring to Phase Change Material 2 in Table 1, when the doping concentration of element Hf is 6.5% and the doping concentration of element N is 5%, the crystallization temperature of Phase Change Material 2 is 35°C higher than that of Phase Change Material 1 (undoped with N) in Table 1. The low resistance of Phase Change Material 2 is more than 100 times higher than that of Phase Change Material 4 (Hf 2% + N 2%) in Table 1, and the low resistance of Phase Change Material 2 is more than 5 times higher than that of Phase Change Material 3 (Hf 4% + N 4%) in Table 1. This causes a phenomenon in which the reading window deteriorates to some extent. When the atomic percentage of element Hf exceeds 6.5% and the atomic percentage of element N or element C exceeds 5.0%, the crystallization temperature increases further. In this case, under certain back-end obline heat treatment conditions, the low resistance of the Phase Change Material layer increases, and the reading window of the Phase Change Member decreases. In this embodiment of the present disclosure, the atomic percentage of element Hf is found to be between 1.5% and 6.5%, and the atomic percentage of element N or element C is between 1% and 5%, which is important to ensure that the phase transition member exhibits a large reading window.

[0055] Furthermore, as mentioned above, the melting points of the HfN and HfC compounds are 3310°C and 3900°C, respectively, indicating high chemical stability.

[0056] The high melting points of HfN and HfC compounds ensure their stability during the RESET (approximately 600°C) melting procedure of the phase change material. The stable clusters of HfN and HfC compounds prevent elemental segregation and phase separation in the GeSbTe phase change base material. These factors contribute to extending the lifespan of the phase change component.

[0057] (2) When the second doping element is element In or element Ga, elements In and Ga tend to form metal-metal bonds with metallic elements such as element Hf, thereby increasing the bonding strength between the phase change material layer and the other functional layer. This is because elements In and Ga have lower melting points (<200°C) at room temperature compared to other solid metallic elements, and elements In and Ga have strong diffusivity. Thus, elements In and Ga form metal-metal bonds with metallic elements in the other functional layer to form an alloy, improving the adhesion between the phase change material and the other functional layer containing metallic elements. For example, the “other functional layer” in this application may be a barrier layer or adhesive layer in the following phase change memory chip.

[0058] In this embodiment of the present disclosure, the mean square displacements of elements Hf, In, and Ga in the Ge-Sb-Te phase transition base material are calculated according to the first principle. As shown in Figures 2 to 4, the mean square displacements of elements In and Ga in the Ge-Sb-Te phase transition base material system are large. This indicates that, under ambient temperature conditions, elements In and Ga are more readily spread, which facilitates the formation of alloys between elements In and Ga and metallic elements in other functional layers.

[0059] For example, if another functional layer contains metallic elements such as W, Ti, Ge, Ta, Hf, In, Ga, Al, Cu, Co, and Mo, elements In and Ga readily bond with the metallic elements to form alloys, creating metal-metal bonds that improve adhesion between the phase change material and the other functional layer, thereby enhancing the adhesion of the phase change material layer.

[0060] In this embodiment of the disclosure, relevant tests are further performed on the adhesion between the W electrode and the phase-change material layer, corresponding to certain phase-change materials that are doped with element In and those that are not doped with element In. See Table 2. These phase-change materials are, respectively, (a) Hf-GeSbTe, a phase-change material in which only the element Hf is doped into the Ge1Sb4Te6 phase-change base material, meaning that the atomic percentage of Hf is 5%; (b) In-GeSbTe, a phase-change material in which only the element In is doped into the Ge1Sb4Te6 phase-change base material, meaning that the atomic percentage of In is 3%; and (c) InHf-GeSbTe, a phase-change material in which both the element Hf and the element In are doped into the Ge1Sb4Te6 phase-change base material, meaning that the atomic percentages of Hf and In are 3% and 2%, respectively.

[0061] [Table 2]

[0062] Table 2 shows that, based on the specified range of 1% to 5% atomic percentage of element In, a higher adhesion force exists between the InHf-GeSbTe phase transition material layer, which is doped with both element Hf and element In, and the W electrode, compared to the Hf-GeSbTe phase transition material layer doped with only Hf and the In-GeSbTe phase transition material layer doped with only In. As a result, the interfacial adhesion is improved, and the adhesion force of the phase transition material layer increases.

[0063] Furthermore, studies have shown that when the element In or element Ga is doped together with the element Hf into the GeSbTe phase-change base material, the phase-change member can more reliably exhibit long-life characteristics. To support this conclusion, in this embodiment of the present disclosure, the bonding strengths of the elements Hf, In, and Ga with the elements Ge, Sb, and Te, as well as the self-bonding strengths of the elements Hf, In, and Ga, are further tested. The unit of bonding strength is kJ / mol. See Table 3 for the test results.

[0064] [Table 3]

[0065] As shown in Table 3, the elements Hf, In, and Ga form covalent bonds with each other, and Hf, In, and Ga form covalent bonds with Ge, Sb, and Te, respectively, and these covalent bonds have equivalent strength. Therefore, when the element In or Ga is separately doped into the Ge-Sb-Te phase-change base material, the element In or Ga readily forms a solid solution with the Ge-Sb-Te phase-change base material. After electrical operation, elemental segregation of Ge, Sb, and Te cannot be prevented, resulting in a shortened lifespan of the phase-change member. However, in the phase-change material provided in this embodiment of the present disclosure, the element Hf is further introduced when the element In and / or Ga are introduced into the Ge-Sb-Te phase-change base material. The formed HfIn alloy and HfGa alloy each have high melting points, and the HfIn or HfGa alloy remains stable during the RESET (approximately 600°C) melting procedure of the phase transition material. Stable HfIn and HfGa alloy clusters prevent elemental segregation and phase separation of the Ge-Sb-Te phase transition base material, both of which contribute to the phase transition member having long lifespan characteristics. In fact, as mentioned above, if another functional layer adjacent to the phase transition material layer contains the element Hf, the HfIn or HfGa alloy is also extremely significant in terms of enhancing the adhesion of the phase transition material layer.

[0066] In conclusion, the phase change material provided in this embodiment of the present disclosure is a Ge-Sb-Te phase change base material doped with element Hf, further doped with at least one of elements N, C, In, and Ga, thereby increasing the adhesion of the phase change material layer, which is tightly bonded to another adjacent functional layer, reducing the possibility of interfacial delamination, improving the product yield of the phase change memory chip, and avoiding contamination and interference to the production line and production equipment. In particular, the doping amount of element Hf is 1.5% to 6.5%, and the doping amount of at least one of elements N, C, In, and Ga is 1.0% to 5.0%. This improves the adhesion of the phase change material layer and promotes that the phase change member has a large read window and a long lifespan.

[0067] In some embodiments, the phase-change material provided in this embodiment of the disclosure further comprises a third doping element, the third doping element comprising at least one of the elements O, Si, B, Sn, Bi, Cd, Pb, Zr, Zn, Cr, Al, Sc, Y, Ta, Ti, Er, Lu, Ho, Tm, Dy, Tb, Ca, Nd, Pr, Yb, Ca, and Ce. Furthermore, the objective of optimizing the overall performance of the phase-change memory member can be achieved by introducing a specific amount of the third doping element into the phase-change material. The atomic percentage of the third doping element in the phase-change material ranges from 0.01% to 10%.

[0068] In the case of Ge-Sb-Te phase-change base materials, the chemical formula of the Ge-Sb-Te compound may be any of the following chemical formulas.

[0069] Chemical formula 1 is (GeTe 1-a ) x (Sb2Te 3-b ) 1-xwhere x is the atomic percentage, 0<x<1, a and b are parameters related to the atomic weight ratio, 0<a≤1, 0<b≤3, and a=1 and b=3 cannot be satisfied simultaneously. For example, the compound GeTe 1-a means that the ratio of the atomic weight of element Ge to the atomic weight of element Te is 1:1-a, and Sb2Te 3-b means that the ratio of the atomic weight of element Sb to the atomic weight of element Te is 2:3-b. In practice, the compound GeTe 1-a does not exclude that the atomic weight of element Ge and the atomic weight of element Te are 1 and 1-a respectively, and the compound Sb2Te 3-b does not exclude that the atomic weight of element Sb and the atomic weight of element Te are 2 and 3-b respectively.

[0070] Chemical formula 2 is (GeTe 1-c ) x (Sb y Te 1-d ) 1-x where x is the atomic percentage, 0<x<1, y, c, d are parameters related to the atomic weight ratio, y≥2, 0<c≤1, 0<d≤1, and c=1 and d=1 cannot be satisfied simultaneously. For example, the compound GeTe 1-c means that the ratio of the atomic weight of element Ge to the atomic weight of element Te is 1:1-c, and Sb y Te 1-d means that the ratio of the atomic weight of element Sb to the atomic weight of element Te is y:1-d. In practice, the compound GeTe 1-c does not exclude that the atomic weight of element Ge and the atomic weight of element Te are 1 and 1-c respectively, and the compound Sb y Te 1-d does not exclude that the atomic weight of element Sb and the atomic weight of element Te are y and 1-d respectively.

[0071] For example, the value of a includes, but is not limited to, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 and the like.

[0072] The value of b is not limited to these, but includes 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, etc.

[0073] The values ​​of y are not limited to these, but include 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5, 6, 7, 8, 9, 10, etc.

[0074] The value of c is not limited to these, but includes 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, etc.

[0075] The value of d is not limited to these, but includes 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, etc.

[0076] In this embodiment of the Disclosure, the chemical formula of the Ge-Sb-Te phase-change base material is as described above, and the phase-change material layer obtained based on the Ge-Sb-Te phase-change base material in this embodiment of the Disclosure exhibits a more reliably higher adhesive strength than the phase-change material layer obtained based on another Ge-Sb-Te phase-change base material. This is because GeTe, Sb2Te3, and Sb yThis is because all Te(y≧2) are stable compounds having a stable chemical composition ratio. It is considered that the Te single-element material is usually a two-dimensional material, a layered structure is formed by Te-Te bonds, these layers are bonded by van der Waals forces, and the adhesive force is poor. In addition, the melting point (620° C.) of Sb2Te3 is higher than the melting point (450° C.) of the Te single-element material. At high temperatures in the phase change procedure, Te is likely to precipitate to form a two-dimensional material of the Te single-element material, resulting in weakened adhesive force. In this embodiment of the present disclosure, since a, b, c, and d are all greater than 0, the Ge-Sb-Te phase change base material is in a Te-deficient state as compared with the aforementioned stable compound. By suitably reducing the content of elemental Te, the adhesive force of the phase change material layer is promoted to be higher than the adhesive force of the phase change material layer corresponding to the Ge-Sb-Te phase change base material.

[0077] To support the aforementioned conclusion, a related adhesive force test is performed in this embodiment of the present disclosure. The adhesive force between the Te-deficient Ge-Sb-Te phase change base material and the W electrode is 1.14 (arbitrary units), and the adhesive force between the non-Te-deficient Ge-Sb-Te phase change base material and the W electrode is 1 (arbitrary units). It was found that the Te-deficient Ge-Sb-Te phase change base material has stronger adhesive force than the non-Te-deficient Ge-Sb-Te phase change base material.

[0078] In some examples, Chemical Formula 1 of the Ge-Sb-Te phase change base material is (GeTe 1-a ) x (Sb2Te 3-b ) 1-x where 0.2<x≦0.4, and Chemical Formula 2 of the Ge-Sb-Te phase change base material is (GeTe 1-c ) x (Sb y Te 1-d ) 1-x where 0.2<x≦0.4.

[0079] For example, the values ​​of x are not limited to these, but include 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, etc.

[0080] The chemical formula of the Ge-Sb-Te phase change base material is as described above. This ensures that the adhesion strength of the phase change material layer is sufficiently high, and the delay of the phase change member is promoted, thereby extending the lifespan of the phase change member.

[0081] The forms of existence of the aforementioned phase-change material provided in this embodiment of the present disclosure include, but are not limited to, alloy forms, compound forms, phase-bonded forms of single-element material and compound, and phase-bonded forms of single-element material and alloy. The phase-change material layer is prepared based on the various forms of the aforementioned phase-change material.

[0082] For example, the forms in which the phase-change material exists are Ge-Sb-Te ternary compounds / alloys, single-element materials or compounds corresponding to the element Hf, and combinations of phases of single-element materials with compounds corresponding to at least one of the elements N, C, In, and Ga. In this case, the corresponding amounts of the aforementioned single-element materials or compounds are provided based on the atomic percentages and ratios of each element in the phase-change material. The combinations of Ge-Sb-Te ternary compounds / alloys, single-element materials or compounds corresponding to the element Hf, and single-element materials with compounds corresponding to at least one of the elements N, C, In, and Ga do not necessarily have to be mixed, and the three materials are independent of each other for backup. Alternatively, the three materials may be mixed to form a phase-change material in the form of a compound or alloy in a melting process.

[0083] In fact, it is not excluded that the phase-change material may exist in the following forms: a single-element material of element Ge, a single-element material of element Sb, a single-element material of element Te, a single-element material of element Hf, and a phase-bonded form of a single-element material corresponding to at least one of elements N, C, In, and Ga. The corresponding amounts of the single-element material are provided based on the atomic percentages and ratios of each element in the phase-change material. These specific amounts of the single-element material do not need to be mixed and may be independent of each other. Alternatively, these specific amounts of the single-element material may be mixed to form a phase-change material in the form of a compound or alloy in a melting process.

[0084] In a second embodiment of the present disclosure, a phase-change material is further provided. The phase-change material comprises a Ge-Sb-Te phase-change base material and a first doping element and a second doping element doped into the Ge-Sb-Te phase-change base material. The first doping element comprises the element Hf, and the atomic percentage of the first doping element in the phase-change material is between 1.5% and 7%. The second doping element comprises at least one of the elements N, C, In, and Ga, and the atomic percentage of the second doping element in the phase-change material is between 1.0% and 7%. Furthermore, the sum of the atomic percentages of the first doping element and the second doping element is greater than 4% and less than 10%.

[0085] For example, some examples of atomic percentages of the first doping element Hf in phase change materials, but not limited to these, include 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, This includes 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, etc.

[0086] For example, some examples of atomic percentages of the second doping element in phase change materials, though not limited to these, include 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, and 3. This includes 5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, etc.

[0087] The sum of the atomic percentages of the first doping element and the second doping element may be 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, etc.

[0088] The second doping element may be one of the elements N, C, In, and Ga. For example, the second doping element may be N, C, In, or Ga, or it may be any combination of any two or any three of the elements N, C, In, and Ga, or it may contain all four elements.

[0089] For the relevant principles for increasing the adhesion of the phase change material layer when the second doping element is element N, element C, element In, or element Ga, refer to the explanation of the relevant principles of the phase change material in the first embodiment described above. Details will not be explained again here.

[0090] Compared to the phase-change material of the first embodiment, the atomic percentages of element N, element C, element In, or element Ga in the phase-change material of the second embodiment increase (from 1.0% to 7%).

[0091] In this type of phase-change material layer, the doping concentrations of the first and second doping elements must be controlled to within 7%. In addition to increasing the adhesion of the phase-change material layer, ensuring that the phase-change component has high and stable high resistance increases the read window, improves the cycle stability of the phase-change component, extends the life of the phase-change component, and improves the cycle stability of the phase-change component by ensuring that the phase-change component has high and stable low resistance. The reasons are as follows:

[0092] Studies have shown that when the atomic percentages of the first doping element and the second doping element individually exceed 7%, side effects occur, resulting in reduced performance such as the read window and the lifespan of the phase change component.

[0093] An example where the second doping element is element N.

[0094] From the data in Table 5 of Example 5, it can be seen that when the atomic percentage of element Hf is excessively high (above 7%), the high resistance of the phase change element decreases, resulting in a narrow reading window. Furthermore, during the cycle procedure, the high resistance becomes unstable, making separation more likely. As a result, the phase change component is more likely to malfunction due to fatigue. When the atomic percentage of element N is excessively high (above 7%), the low resistance of the phase change component increases abnormally, becoming unstable during the cycle procedure and continuously decreasing during the malfunction procedure. This may be related to segregation caused by thermoelectric accumulation, which tends to occur during the operation procedure.

[0095] As shown in Table 5, when the atomic percentage of element Hf is 8% (exceeding the defined upper limit of 7%), the high resistance of the phase change memory chip becomes low and unstable during the cycle. When the atomic percentage of element N is 8% (exceeding the defined upper limit of 7%), the low resistance becomes high and the low resistance of the phase change memory chip becomes unstable during the cycle. Therefore, in this embodiment of the present disclosure, when the atomic percentage of element Hf and the atomic percentage of element N are separately 7% or less, it is guaranteed that the phase change member has high stability high resistance and the phase change member has high stability low resistance.

[0096] Furthermore, in this type of phase-change material, the sum of the atomic percentages of the first doping element and the second doping element must be greater than 4% and less than 10%. In this case, it is possible to ensure that the phase-change material layer has high adhesive strength and that the phase-change component has a long lifespan and cycle stability. The reasons are as follows:

[0097] Studies have shown that in this type of phase-change material, the lifespan of the phase-change component is related to the doping concentration of Hf and the doping concentration of the second doping element. Performance analysis of phase-change components has shown that the low resistance of the phase-change component is directly proportional to its final fatigue life. As shown in Figure 24, within a certain range, higher low resistance of the phase-change component leads to better fatigue characteristics. The low resistance of the phase-change component is mainly determined by the low resistance of the phase-change material layer and the crystallization temperature. The horizontal and vertical coordinate values ​​in Figure 24 are both obtained using normalized logarithms.

[0098] An example where the second doping element is element N.

[0099] The data in Table 1 shows that as the doping concentrations of element Hf and element N increase, both the low resistance and crystallization temperature of the phase change material layer increase in correspondence (see Phase Change Material 3 and Phase Change Material 4 in Table 1). Consequently, the low resistance of the phase change member also increases, resulting in a longer lifespan for the phase change member.

[0100] Therefore, in order to ensure a long lifespan for the phase change component, it is necessary to make the low resistance of the phase change material layer as high as possible, while maintaining a specific reading window. However, in phase change material 4 in Table 1, the atomic percentage of element Hf in phase change material 4 is 2%, and the atomic percentage of element N in phase change material 4 is 2%. In phase change material 1 in Table 1, the atomic percentage of element Hf in phase change material 1 is 4%, and the atomic percentage of element N in phase change material 1 is 0%. The low-resistance state of the phase change material layer corresponding to the two phase change materials is approximately 400 ohms in both cases, which is much smaller than 1 k ohm, and the sum of the atomic percentages of element Hf and element N in both phase change materials is 4%. Accordingly, in this embodiment of the present disclosure, the sum of the atomic percentages of element Hf and element N is limited to exceed 4%, that is, the sum of the atomic percentages of the first doping element and the second doping element is limited to exceed 4%. This is extremely important for giving the phase change member long-life characteristics.

[0101] A higher sum of the doping concentrations of the first and second doping elements is undesirable. Studies have confirmed that when the sum of the doping concentrations of the first and second doping elements exceeds 10%, side effects occur, and the cycle procedure of the phase change member becomes unstable. This includes an abnormal increase in the low resistance of the phase change member, leading to instability during the cycle procedure. Specifically, the resistance decreases continuously during the cycle procedure, which may be due to segregation caused by thermoelectric accumulation that is likely to occur in the phase change material layer during the operation procedure. An example in which the second doping element is element N is still used. From the data in Table 5 in Example 5, it can be seen that when the atomic percentage of element Hf is 6.5% and the atomic percentage of element N is 5%, the sum of the atomic percentages of the two elements exceeds 10%, resulting in an abnormal increase in low resistance and instability during the cycle procedure. The sum of the atomic percentages of element Hf and element N is expected to be less than 10%.

[0102] In conclusion, in this type of phase-change material of the present disclosure, at least one of the elements N, C, In, and Ga is further doped into the Ge-Sb-Te phase-change base material doped with element Hf, thereby increasing the adhesion of the phase-change material layer, which is tightly combined with another adjacent functional layer, reducing the incidence of interfacial delamination, improving the product yield of the phase-change storage chip, and avoiding contamination and interference to the production line and production equipment. Specifically, the doping amount of element Hf is 1.5% to 7%, the doping amount of at least one of the elements N, C, In, and Ga is 1.0% to 7%, and the sum of the atomic percentages of the two doping elements is between 4% and less than 10%. This improves the adhesion of the phase-change material layer, which helps the phase-change component have a large read window, long life, and cycle stability.

[0103] In some implementations, the phase-change material provided in this embodiment of the disclosure further comprises a third doping element, the third doping element comprising at least one of the elements O, Si, B, Sn, Bi, Cd, Pb, Zr, Zn, Cr, Al, Sc, Y, Ta, Ti, Er, Lu, Ho, Tm, Dy, Tb, Ca, Nd, Pr, Yb, Ca, and Ce. Furthermore, the objective of optimizing the overall performance of the phase-change memory member can be achieved by introducing a specific amount of the third doping element into the phase-change material. The atomic percentage of the third doping element in the phase-change material ranges from 0.01% to 10%.

[0104] In the case of Ge-Sb-Te phase-change base materials, the chemical formula of the Ge-Sb-Te compound may be any of the following chemical formulas.

[0105] Chemical formula 1 is (GeTe 1-a ) x (Sb2Te 3-b ) 1-xwherein x is an atomic percentage, 0<x<1, a and b are parameters related to atomic weight ratios, 0<a≦1, 0<b≦3, and a=1 and b=3 cannot be satisfied simultaneously.

[0106] Chemical Formula 2 is (GeTe 1-c ) x (Sb y Te 1-d ) 1-x wherein x is an atomic percentage, 0<x<1, y, c and d are parameters related to atomic weight ratios, y≧2, 0<c≦1, 0<d≦1, and c=1 and d=1 cannot be satisfied simultaneously.

[0107] For example, for the parameter values in Chemical Formula 1 and Chemical Formula 2 of the Ge-Sb-Te phase change base material and the related descriptions, reference is made to the relevant description of the phase change material in the first embodiment. The details will not be described again here.

[0108] In this embodiment of the present disclosure, the chemical formula of the Ge-Sb-Te phase change base material is as described above, and it is ensured that the phase change material layer obtained based on the Ge-Sb-Te phase change base material in this embodiment of the present disclosure has higher adhesion than phase change material layers obtained based on other Ge-Sb-Te phase change base materials. This is because GeTe, Sb2Te3 and Sb yThis is because all Te (y≧2) are stable compounds with a stable chemical composition ratio. It is considered that the single-element material of Te is a typical two-dimensional material, a layered structure is formed via Te-Te bonds, these layers are bonded by van der Waals forces, and the adhesive force is poor. In addition, the melting point of Sb₂Te₃ (620°C) is higher than the melting point of the single-element material of Te (450°C). At high temperatures during the phase change procedure, Te has a high tendency to precipitate and form a two-dimensional material of the single-element material of Te, resulting in weakened adhesive force. In this embodiment of the present disclosure, since a, b, c, and d are all greater than 0, the Ge-Sb-Te phase change base material is in a Te-deficient state compared with the aforementioned stable compound. By suitably reducing the content of elemental Te, it is ensured that the adhesive force of the phase change material layer is sufficiently enhanced.

[0109] In addition, for the related adhesive force test of the Ge-Sb-Te phase change base material, reference is still made to the related description of the phase change material in the first embodiment. The details will not be described again here.

[0110] In some examples, Chemical Formula 1 of the Ge-Sb-Te phase change base material is (GeTe 1-a ) x (Sb₂Te 3-b ) 1-x where 0.2<x≦0.4, and Chemical Formula 2 of the Ge-Sb-Te phase change base material is (GeTe 1-c ) x (Sb y Te 1-d ) 1-x where 0.2<x≦0.4.

[0111] For example, the value of x includes, but is not limited to, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, and the like.

[0112] When 0.2<x≦0.4, the corresponding Chemical Formula 1 or Chemical Formula 2 of the Ge-Sb-Te phase-change base material can instead be expressed in another way as follows: Ge x Sb y Te 1-x-y (where x and y each represent the atomic percentage of the corresponding element, with 6%<x<15% and 35%<y<45% (or Ge x Sb y Te 100-x-y (where x and y are each the mass amount of the corresponding atom, 6<x<15 and 35<y<45)).

[0113] For example, in the Ge-Sb-Te phase-change base material, based on the aforementioned chemical formula being satisfied, the ratio between the atomic percentages of element Ge, element Sb, and element Te includes, but is not limited to, 1:4:5, 1:4:6, 1:4:7, etc., and the corresponding GeSbTe compounds are referred to as GeSbTe145 (or Ge1Sb4Te5 or GST145), GeSbTe146 (or Ge1Sb4Te6 or GST146), and GeSbTe147 (or Ge1Sb4Te7 or GST147), respectively.

[0114] The chemical formula of the Ge-Sb-Te phase-change base material is as described above, which not only makes the adhesive force of the phase-change material layer sufficiently high, but also ensures that the delay of the phase-change member is reduced and the service life of the phase-change member is extended.

[0115] In this embodiment of the present disclosure, relevant tests are performed on the effects of the contents of element Ge and element Sb in the Ge-Sb-Te phase-change base material on adhesive force, delay, and service life. The test results show that the atomic percentage of element Sb is an important factor that determines the speed of the phase-change member. Since the single-element material of Sb has a low crystallization temperature and a high growth rate, the atomic percentage of element Sb is positively correlated with the SET performance of the phase-change member. Theoretically, it is shown that the higher the atomic percentage of element Sb, the smaller the delay of the phase-change member.

[0116] Experiments have shown that when the atomic percentage of Sb in a Ge-Sb-Te phase transition base material is greater than 35% (satisfying the aforementioned stoichiometric ratio x ≤ 0.4), the crystallization temperature of the single-element Sb material is low and the growth rate is fast, allowing the phase transition delay of the component to be less than 100 ns. However, a high atomic percentage of Sb is undesirable. When the atomic percentage of Sb in a Ge-Sb-Te phase transition base material exceeds 45% (satisfying the aforementioned stoichiometric ratio x > 0.2), the amount of stable compounds formed by the bonding of Sb and Te relatively decreases, resulting in a relatively excess of single-element Sb material, lower stability, and consequently, a somewhat shorter lifetime of the phase transition component. It is found that to promote both low delay and long lifetime of the phase transition component, the atomic percentage of Sb should be limited to between 35% and 45%.

[0117] Regarding the element Ge, experiments have shown that when the atomic percentage of element Ge exceeds 15% and the concentration of element Ge is excessively high, the delay of the phase change component slows down to some extent. On the other hand, when the atomic percentage of element Ge falls below 6% (which satisfies the aforementioned stoichiometric ratio x > 0.2) and the concentration of element Ge becomes excessively low, the adhesive strength of the phase change material layer decreases, making it extremely difficult to optimize the mass production process. It is understood that in order to promote high adhesive strength of the phase change material layer and low delay of the phase change component, the atomic percentage of Ge should be limited to between 6% and 15%.

[0118] Furthermore, the mode of existence of the phase change material provided in the second embodiment is described in the relevant section on the phase change material in the first embodiment. Details will not be explained again here.

[0119] In this embodiment of the present disclosure, it is found that the corresponding bonding relationships between different elements in the phase change material and the performance of the key members (speed, lifespan, window, and adhesion) are defined, the stoichiometric ratios of each element are adjusted, the performance of the phase change memory chip is balanced and optimized, and better overall performance of the phase change memory chip is ensured.

[0120] In one embodiment of the present disclosure, a phase-change memory chip is further provided. The phase-change memory chip comprises a plurality of phase-change memory units, each of which comprises a phase-change material layer 100, the phase-change material layer 100 being prepared using one of the aforementioned phase-change materials.

[0121] A phase-change memory chip is also referred to as a phase-change memory. The phase-change memory chip provided in this embodiment of the Disclosure is prepared based on the phase-change material layer 100 of the phase-change memory chip provided in this embodiment of the Disclosure, and the phase-change memory chip has all the advantages of the phase-change material provided in this embodiment of the Disclosure.

[0122] The phase change memory unit is placed on the substrate 004. In some examples, as shown in Figure 5, the phase change memory unit has, in addition to the phase change material layer 100, an upper electrode 501, a bottom electrode 502, and an insulating layer 400. In the bottom-up direction, the substrate 004, bottom electrode 502, phase change material layer 100, and upper electrode 501 are stacked in this order, and the insulating layer 400 surrounds at least the outside of the phase change material layer 100.

[0123] In some other examples, as shown in Figure 6, the phase-change memory unit further includes an upper electrode 501, a bottom electrode 502, an insulating layer 400, and a barrier layer 300, in addition to the aforementioned phase-change material layer 100. In the bottom-up direction, the substrate 004, bottom electrode 502, barrier layer 300, phase-change material layer 100, barrier layer 300, and upper electrode 501 are stacked in this order, with the insulating layer 400 surrounding at least the outside of the phase-change material layer 100 and the barrier layer 300.

[0124] For example, the barrier layer material used in the barrier layer 300 includes at least one single-element material of the element W, element Ti, element Ge, element Ta, element Hf, element In, element Ga, element Al, element Cu, element Co, and element Mo, nitrides of the aforementioned elements, and carbides of the aforementioned elements.

[0125] An example is used in which the second doping element in the phase change material layer 100 is element N or element C. Element N or element C can bond with the aforementioned metal element in the barrier layer 300, forming a nonmetal-metal ion bond, improving the bonding strength between the adhesive layer 200 and the barrier layer 300, and reducing the possibility of interfacial delamination between the adhesive layer 200 and the barrier layer 300 during the processing procedure.

[0126] Furthermore, as shown in Figures 7 and 8, the phase-change memory unit provided in this embodiment of the present disclosure further comprises an adhesive layer 200. The adhesive layer 200 is arranged in a laminated configuration on at least one surface of the phase-change material layer 100 and is configured to enhance the adhesion between the phase-change material layer 100 and adjacent functional layers.

[0127] For example, the adhesive layer 200 may be located on the surface of the phase change material layer 100, facing the upper electrode 501, or on the surface of the phase change material layer 100, facing the bottom electrode 502, or separately on the two opposing surfaces of the phase change material layer 100.

[0128] The adhesive layer 200 is applied to at least one surface of the phase-change material layer 100 to increase the adhesion between the phase-change material layer 100 and the adjacent functional layer. The adjacent functional layer may be a barrier layer 300 or an electrode layer.

[0129] In the phase-change memory chip provided in this embodiment of the present disclosure, the phase-change memory material is improved, the structure of the phase-change memory chip is improved, an adhesive layer 200 is added to the phase-change memory chip, the adhesion between the phase-change material layer 100 and the adjacent functional layer is further improved, the possibility of interfacial delamination is greatly reduced, the product yield of the phase-change memory unit is improved, and contamination and interference to the production line can be avoided.

[0130] The adhesive layer 200 is prepared using adhesive layer raw materials. In some embodiments, the adhesive layer raw materials include at least one nitride and / or carbide of the target element. The target element is selected from at least one of W, Ti, Ge, Ta, Hf, In, Ga, Al, Cu, Co, and Mo. An example is used where the target element is W. The adhesive layer raw materials may be tungsten nitride or tungsten carbide.

[0131] If the second doping element in the phase change material layer 100 is element N or element C, then element N or element C in the adhesive layer 200 and the target element can form a nonmetal-metal ion bond, improving the adhesion between the adhesive layer 200 and the phase change material layer 100, increasing the interfacial adhesion, and reducing the likelihood of interfacial delamination between the adhesive layer 200 and the phase change material layer 100 during the processing procedure.

[0132] If the second doping element in the phase change material layer 100 is element In or element Ga, element In or element Ga can combine with the target element in the adhesive layer 200 to form an alloy, forming a metal-metal bond, improving the adhesion between the adhesive layer 200 and the phase change material layer 100, increasing the interfacial adhesion, and reducing the likelihood of interfacial delamination between the adhesive layer 200 and the phase change material layer 100 during the processing procedure.

[0133] By using the aforementioned adhesive layer raw materials, it is possible to enhance the interfacial bonding function and bonding strength between the phase change material layer and the adhesive layer, thereby preventing a decrease in member yield caused by the phase change material layer detaching from the interface of the barrier layer.

[0134] To verify stronger interfacial adhesion in phase-change memory chips having adhesive layers, this embodiment of the present disclosure provides several types of phase-change materials for relevant adhesion strength tests. These phase-change materials are as follows: (d) Phase-change material HfGST, meaning that the phase-change base material of Ge1Sb4Te6 is doped with element Hf only, with an atomic percentage of Hf of 3%; and (e) Phase-change material NHfGST, meaning that the phase-change base material of Ge1Sb4Te6 is doped with both element Hf and element N, with atomic percentages of Hf and N being 3% and 2%, respectively. The adhesion between the phase-change material layer corresponding to the phase-change material and the W electrode was evaluated. See Table 2 for the test results.

[0135] The adhesive strength between the phase change material layer corresponding to the phase change material and the W electrode, and the adhesive strength between the phase change material layer corresponding to the phase change material and the W2N material were tested separately. See Table 4 for the test results.

[0136] [Table 4]

[0137] Table 4 shows that, based on the fact that the atomic percentages of element Hf and element N satisfy their respective limited atomic percentage ranges, the adhesion between the phase transition material layer doped with both element Hf and element N and the W electrode in this application is considerably greater than the adhesion between the phase transition material layer not doped with element N and the W electrode, compared to a phase transition material layer doped with element Hf alone. Furthermore, the adhesion between the phase transition material layer doped with both element Hf and element N and the W electrode is slightly less than the adhesion between the phase transition material layer doped with both element Hf and element N and the adhesive layer W2N. It can be seen that the interfacial adhesion of the phase transition material layer can be further improved by adding an additional adhesive layer.

[0138] In some other embodiments, the adhesive layer raw material includes a Ge-Sb-Te phase change material doped with a fourth doping element, and the adhesive layer raw material is different from the phase change material used for the phase change material layer. The fourth doping element is selected from at least one of the element Hf, the element N, the element C, the element In, and the element Ga, and the atomic percentage of the fourth doping element in the adhesive layer raw material is 0.01% to 20%, and may further be 0.01% to 10%.

[0139] The chemical formula of the related Ge-Sb-Te phase change material is (GeTe 1-a ) x (Sb2Te 3-b ) 1-x , where 0<x<1, 0<a≦1, 0<b≦3, and a=1 and b=1 cannot be satisfied at the same time (x, a, and b are all parameters representing atomic percentages). Alternatively, the chemical formula of the Ge-Sb-Te phase change material is (GeTe 1-c ) x (Sb y Te 1-d ) 1-x which may be expressed as, where 0<x<1, y≧2, 0<c≦1, 0<d≦1, and c=1 and d=1 cannot be satisfied at the same time (x, y, c, and d are all parameters representing atomic percentages).

[0140] For example, simplified formulas of some applicable adhesive layer raw materials may be expressed as NHfGeSbTe, CHfGeSbTe, InHfGeSbTe, GaHfGeSbTe, HfGeSbTe, NGeSbTe, CGeSbTe, InGeSbTe, GaGeSbTe, and the like.

[0141] Since the doping amount of the fourth doping element in the Ge-Sb-Te phase change material is within the aforementioned range, the Ge-Sb-Te phase change material doped with the fourth doping material is different from the phase change material in the phase change material layer 100, and mainly has an interface adhesion function.

[0142] As described above, the adhesive layer 200 is placed between the phase change material layer 100 and the adjacent functional layer. The adjacent functional layer may be a barrier layer 300, or an electrode layer (including at least one of an upper electrode 501 and a bottom electrode 502).

[0143] In the solution, the phase change memory unit includes a barrier layer 300, and the adhesive layer 200 is positioned between the phase change material layer 100 and the barrier layer 300 and configured to enhance the adhesive strength between the phase change material layer 100 and the barrier layer 300.

[0144] In the phase change memory unit, the barrier layer 300 has the function of preventing elements in the phase change material layer 100 from spreading to the electrode layer. The adhesive layer 200 is placed between the phase change material layer 100 and the barrier layer 300, effectively suppressing delamination between the phase change material layer 100 and the barrier layer 300.

[0145] In some examples, as shown in Figure 7, there are two barrier layers 300, each positioned on two opposing sides of the phase-change material layer 100. In this case, there may be two adhesive layers 200. One adhesive layer 200 is positioned between the first surface of the phase-change material layer 100 and one barrier layer 300, and the other adhesive layer 200 is positioned between the second surface of the phase-change material layer 100 and the other barrier layer 300.

[0146] For example, the barrier layer material used in the barrier layer 300 includes at least one single-element material of the element W, element Ti, element Ge, element Ta, element Hf, element In, element Ga, element Al, element Cu, element Co, and element Mo, nitrides of the aforementioned elements, and carbides of the aforementioned elements. Clearly, the barrier layer material is different from the adhesive layer material.

[0147] When the second doping element in the phase change material layer 100 is element N or element C, element N or element C and the metallic element in the barrier layer 300 can form a nonmetal-metal ion bond, improving the bonding strength between the barrier layer 300 and the phase change material layer 100, increasing the interfacial adhesion, and reducing the possibility of interfacial delamination between the barrier layer 300 and the phase change material layer 100 during the processing procedure.

[0148] If the second doping element in the phase change material layer 100 is element In or element Ga, element In or element Ga can combine with the metallic element in the barrier layer 300 to form an alloy, forming a metal-metal bond, improving the bonding strength between the barrier layer 300 and the phase change material layer 100, increasing the interfacial adhesion, and reducing the possibility of interfacial delamination between the barrier layer 300 and the phase change material layer 100 during the processing procedure.

[0149] In the aforementioned solution, in addition to the aforementioned phase change material layer 100, adhesive layer 200, and barrier layer 300, the phase change memory unit may further have an upper electrode 501, a bottom electrode 502, and an insulating layer 400. In one embodiment, as shown in Figure 7, in the bottom-up direction, the substrate 004, bottom electrode 502, barrier layer 300, adhesive layer 200, phase change material layer 100, adhesive layer 200, barrier layer 300, and upper electrode 501 are arranged in this order in a stacked manner, and the insulating layer 400 surrounds at least the outside of the phase change material layer 100, adhesive layer 200, and barrier layer 300.

[0150] In some examples, the thickness of the barrier layer 300 and the thickness of the adhesive layer 200 are, separately, 1 nm to 8 nm, and this includes, but is not limited to, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, etc. For example, the thickness of both the barrier layer 300 and the adhesive layer 200 may be 2 nm.

[0151] In an alternative solution, the phase change memory unit has an electrode layer, and an adhesive layer 200 is placed between the phase change material layer 100 and the electrode layer, configured to enhance the adhesion between the phase change material layer 100 and the electrode layer. The adhesive layer 200 is placed between the phase change material layer 100 and the corresponding electrode layer, effectively suppressing delamination between the phase change material layer 100 and the electrode layer.

[0152] In the aforementioned solution, in addition to the phase change material layer 100 and the adhesive layer 200, the phase change memory unit may further have an upper electrode 501, a bottom electrode 502, and an insulating layer 400. In one embodiment, as shown in Figure 8, in the bottom-up direction, the substrate 004, the bottom electrode 502, the adhesive layer 200, the phase change material layer 100, the adhesive layer 200, and the upper electrode 501 are arranged in this order in a stacked manner, and the insulating layer 400 surrounds at least the outside of the phase change material layer 100 and the adhesive layer 200.

[0153] In the aforementioned phase-change memory unit, the structure of the phase-change memory unit is not limited to this, but includes a restricting structure, a T-shaped structure, a U-shaped groove structure, an L-shaped structure, and the like.

[0154] In some embodiments, the phase-change memory chip provided in this embodiment of the present disclosure further comprises a plurality of selector units, the selector units and the phase-change memory unit arranged in series. The selector units are used as switching members for the phase-change memory unit to effectively suppress leakage currents that occur during the operation of the phase-change memory chip.

[0155] See Figure 9. The selector unit has a selector layer 600, and the selector material used for the selector layer 600 includes at least one of the S-series selector material, Se-series selector material, and Te-series selector material. All of the aforementioned S-series selector material, Se-series selector material, and Te-series selector material can be any currently known or commercially available gate material. Embodiments will not be described one by one in this application. The aforementioned selector material may be a binary compound, a ternary compound, or any other multi-element compound containing more elements.

[0156] Furthermore, the selector material further comprises a fifth doping element, the fifth doping element being selected from at least one of the following: element B, element Al, element Ga, element In, element C, element Si, element Ge, element Sn, element N, element P, element As, element Sb, element Bi, element O, element Au, element Hf, element Pd, element Cu, element Co, element Ag, element Pt, element Sc, element Ti, and element Ta. The atomic percentage of the fifth doping element in the selector material may be from 0.01% to 20%, and further from 0.01% to 10%.

[0157] In some examples, the fifth doping element includes at least one of the elements B, Al, Ga, In, C, Si, Ge, Sn, N, P, As, Sb, Bi, and O, and further includes at least one of the elements Au, Hf, Pd, Cu, Co, Ag, Pt, Sc, Ti, and Ta.

[0158] The fifth doping element is doped into the selector material, and the selector layer 600 has advantages such as low leakage current, strong thermal stability, and long cycle life.

[0159] The thickness of the selector layer 600 may range from 10 nm to 50 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm. The thickness of the selector layer 600 is determined based on the electrical characteristics of the phase change memory unit connected in series with the selector layer 600, ensuring that the selector unit maintains the expected switching characteristics.

[0160] In some examples, as shown in Figures 9 to 12, the selector unit may include only the selector layer 600, which is integrated into the phase change memory unit. The selector layer 600 and the phase change material layer 100 in the phase change memory unit are connected in series via an intermediate electrode 503.

[0161] In some examples, the selector unit is independent of the corresponding phase-change memory unit (not shown in the figure). In this example, the selector unit may have a substrate, a bottom electrode, a selector layer, and an upper electrode, which are arranged in a stacked configuration, continuously from bottom to top, and the outside of the selector layer is further surrounded by an insulating layer. The electrode layer of the selector unit and the electrode layer of the corresponding phase-change memory unit may be connected in series using a conductor (e.g., a copper wiring cable).

[0162] The phase-change memory chip provided in this embodiment of the present disclosure may be prepared using a thin-film deposition process, a photolithography process, an etching process, and the like. Multiple functional layers in the phase-change memory chip, such as a phase-change material layer 100, an adhesive layer 200, a barrier layer 300, and a selector layer 600, may all be prepared using a thin-film deposition process.

[0163] For example, some applicable thin-film deposition processes include, but are not limited to, atomic layer deposition (ALD), physical vapor deposition (PVD), and chemical vapor deposition (CVD). For instance, the aforementioned functional layer may be prepared using methods such as plasma-enhanced chemical vapor deposition (PECVD), magnetron sputtering, or electron beam deposition.

[0164] Magnetron sputtering is a type of physical vapor deposition process that offers advantages such as strong adhesion and a wide range of materials that can be prepared. For example, in this embodiment of the present disclosure, a functional layer may be formed using the magnetron sputtering method. The sputtering gas used in the magnetron sputtering method includes, but is not limited to, at least one of argon (Ar), krypton (Kr), xenon (Xe), neon (Ne), and nitrogen (N2).

[0165] The substrate 004 in the phase change memory unit and some gate tube units includes, but is not limited to, silicon dioxide substrates, silicon carbide substrates, silicon wafer substrates, sapphire substrates, diamond substrates, and the like.

[0166] The electrode materials for the electrodes (upper electrode 501, bottom electrode 502, and intermediate electrode 503) relating to the phase change memory unit and several selector units include, but are not limited to, tungsten titanium TiW (e.g., Ti3W7), tungsten W, aluminum Al, titanium nitride TiN, titanium Ti, tantalum Ta, silver Ag, platinum Pt, carbon Cu, copper Cu, ruthenium Ru, gold Au, cobalt Co, chromium Cr, nickel Ni, iridium Ir, palladium Pd, rhodium Rh, and the like.

[0167] The electrode material may be deposited onto the corresponding electrode layer using a process such as physical vapor deposition (PVD) (e.g., magnetron sputtering).

[0168] The insulating layer 400 in the phase change memory unit and some selector units is configured to provide insulating and heat insulating functions, and the insulating and heat insulating materials used in the insulating layer 400 include, but are not limited to, silicon nitride (Si3N4), silicon carbide (SiC), silicon dioxide (SiO2), etc. The insulating and heat insulating material may be deposited in the insulating layer 400 using a chemical vapor deposition (CVD) method, for example, a plasma-enhanced chemical vapor deposition (PECVD) method.

[0169] In some embodiments, as shown in Figures 9 to 12, the insulating layer 400 includes a first insulating layer 401 and a second insulating layer 402. The first insulating layer 401 surrounds at least the outer surface of the phase change material layer 100 and may further surround the outer surfaces of the barrier layer 300, the adhesive layer 200, and the upper electrode 501. The second insulating layer 402 surrounds the outer surface of the first insulating layer 401.

[0170] For example, the first insulating layer 401 is silicon nitride Si3N4, silicon carbide SiC, etc., and the thickness of the first insulating layer 401 is greater than 1 nm, for example, 2 nm to 3 nm. The second insulating layer 402 is a compound formed by the element Si and at least one of the elements N, C, and O, for example, at least one of silicon nitride Si3N4, silicon carbide SiC, and silicon dioxide SiO2, and the thickness of the second insulating layer 402 is greater than 1 nm, for example, 2 nm to 3 nm.

[0171] The first insulating layer 401 and the second insulating layer 402 are arranged on the outside of the phase change material layer 100, from the inside out, to optimize insulating isolation and thermal isolation.

[0172] In some examples, as shown in Figures 9 to 12, the insulating layer includes a third insulating layer 403 and a fourth insulating layer 404. The third insulating layer 403 surrounds at least the outer surface of the selector layer 600 and may also surround the outer surfaces of the intermediate electrode 503 and the bottom electrode 502. The fourth insulating layer 404 surrounds the outer surface of the third insulating layer 403.

[0173] For example, the third insulating layer 403 is silicon nitride Si3N4, silicon carbide SiC, etc., and the thickness of the third insulating layer 403 is greater than 1 nm, for example, 2 nm to 3 nm. The fourth insulating layer 404 is a compound formed of element Si and at least one of element N, element C, and element O, for example, at least one of silicon nitride Si3N4, silicon carbide SiC, and silicon dioxide SiO2, and the thickness of the fourth insulating layer 404 is greater than 1 nm.

[0174] For example, the thickness of the single-layer fourth insulating layer 404 may be 2 nm to 3 nm. In some embodiments, the fourth insulating layer 404 may instead be arranged as a two-layer structure that is sequentially surrounded from the inside out. The materials of the two layers in the structure are different, and the thickness of the two-layer fourth insulating layer 404 may be 2 nm to 15 nm.

[0175] The third insulating layer 403 and the fourth insulating layer 404 are arranged on the outside of the selector layer 600, from inside to outside, to optimize insulating and thermal isolation.

[0176] The structural configurations of the phase-change memory chip provided in this embodiment of the present disclosure include, but are not limited to, a 1S1R (1 selector, 1 register) structure and a 1SnR (1 selector, n registers) structure. In a 1S1R phase-change memory chip, one selector unit corresponds to and controls one phase-change memory unit. In a 1SnR phase-change memory chip, one selector unit corresponds to n phase-change memory units, which are controlled simultaneously.

[0177] In some examples, the structure of the phase-change memory chip in this embodiment of the present disclosure may be a 1S1R structure, where each group of selector units and phase-change memory units connected in series is defined as a single memory subunit 001. As shown in Figure 13, a 1S1R type phase-change memory chip includes a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. In fact, the phase-change memory chip further includes peripheral control circuits.

[0178] Multiple memory subunits 001 form a phase-change memory array. The multiple memory subunits 001 are arranged in an array, and multiple word lines 002 are distributed in parallel with spacing between them, each word line 002 extending in a first direction, and multiple bit lines 003 are distributed in parallel with spacing between them, each bit line 003 extending in a second direction. There is an angle between the first direction and the second direction, and this angle is greater than 0° and less than or equal to 90°.

[0179] For example, the angle between the first direction and the second direction is equal to 90°, and as a result, multiple word lines 002 are arranged in sequential rows, and multiple bit lines 003 are arranged in sequential columns, and the multiple rows of word lines 002 and the multiple columns of bit lines 003 work together to form an array that matches multiple storage subunits 001. Each storage subunit 001 is placed in a matrix subunit that includes word lines 002 and bit lines 003 (i.e., placed in the overlapping region between word lines 002 and bit lines 003), each storage subunit 001 is connected to the bit line 003 of the corresponding column via the upper electrode 501 of the storage subunit 001, and each storage subunit 001 is connected to the word line 002 of the corresponding row via the bottom electrode 502 of the storage subunit 001.

[0180] During application, multiple word lines 002 arranged in rows are connected to row selection circuit A1, which is further driven by row voltage control circuit B1. Multiple bit lines 003 arranged in columns are connected to column selection circuit A2, which is further driven by column voltage control circuit B2. A read / write circuit C is separately connected to either row voltage control circuit B1 or column voltage control circuit B2 by receiving commands from the processor. In this way, the read / write circuit C controls either row selection circuit A1 or column selection circuit A2 by receiving commands from the processor via row voltage control circuit B1 or column voltage control circuit B2, and performs read / write operations on the phase-change storage unit in the selected storage subunit 001.

[0181] In a method where read / write operations are performed in a phase-change memory unit, a selector unit is used as a switch component. If memory subunit 001 is not selected by both row selection circuit A1 and column selection circuit A2, the selector unit corresponding to memory subunit 001 is turned off, thus avoiding the influence of leakage current on other units.

[0182] In the phase-change memory chip provided in this embodiment of the present disclosure, three-dimensional stacking is performed on a three-dimensional stacked memory chip, forming an N-layer structure (N≧1) in the vertical direction, and the storage density of the three-dimensional stacked memory is 4F 2 It will reach ×N, where F is the feature size of the semiconductor process.

[0183] The following describes the structure of some phase-change memory chips provided in embodiments of this disclosure, using examples, with reference to a solution in which the phase-change memory chip has a selector layer 600 and the selector layer 600 is integrated into a phase-change memory unit.

[0184] In Example 1, Figure 9 shows a 1S1R type phase-change memory chip. This phase-change memory chip is placed on a substrate 004 and has a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. The plurality of memory subunits 001 are arranged in an array, the plurality of word lines 002 are arranged in sequential rows, and the plurality of bit lines 003 are arranged in sequential columns. Each memory subunit 001 is connected to the bit line 003 of the corresponding column via the upper electrode 501 of the memory subunit 001, and each memory subunit 001 is connected to the word line 002 of the corresponding row via the bottom electrode 502 of the memory subunit 001.

[0185] Each memory subunit 001 has a bottom electrode 502, a selector layer 600, an intermediate electrode 503, a barrier layer 300, a phase change material layer 100, another barrier layer 300, and an upper electrode 501, which are arranged sequentially from bottom to top in a stacked configuration. Adjacent memory subunits 001 are separated from each other by insulating layers. Specifically, for each memory subunit 001, the outer sides of the barrier layer 300, the phase change material layer 100, the barrier layer 300, and the upper electrode 501 are sequentially surrounded from the inside to the outside by a first insulating layer 401 and a second insulating layer 402, and the outer sides of the bottom electrode 502, the selector layer 600, and the intermediate electrode 503 are sequentially surrounded from the inside to the outside by a third insulating layer 403 and a fourth insulating layer 404.

[0186] In the phase-change memory chip provided in Example 1, the phase-change material layer 100 of the phase-change memory chip uses the improved phase-change material provided in the aforementioned embodiments of this disclosure, thereby effectively improving the adhesion between the phase-change material layer 100 and the barrier layer 300.

[0187] In Example 2, Figure 10 shows a 1S1R type phase-change memory chip. The phase-change memory chip is placed on a substrate 004 and has a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. The plurality of memory subunits 001 are arranged in an array, the plurality of word lines 002 are arranged in sequential rows, and the plurality of bit lines 003 are arranged in sequential columns. Each memory subunit 001 is connected to the bit line 003 of the corresponding column via the upper electrode 501 of the memory subunit 001, and each memory subunit 001 is connected to the word line 002 of the corresponding row via the bottom electrode 502 of the memory subunit 001.

[0188] Each memory subunit 001 has a bottom electrode 502, a selector layer 600, an intermediate electrode 503, a barrier layer 300, an adhesive layer 200, a phase change material layer 100, an adhesive layer 200, a barrier layer 300, and an upper electrode 501, which are arranged sequentially from bottom to top in a stacked configuration. Adjacent memory subunits 001 are separated from each other via insulating layers. Specifically, in each memory subunit 001, the outer sides of the barrier layer 300, adhesive layer 200, phase change material layer 100, adhesive layer 200, barrier layer 300, and upper electrode 501 are sequentially surrounded from the inside to the outside by a first insulating layer 401 and a second insulating layer 402, and the outer sides of the bottom electrode 502, selector layer 600, and intermediate electrode 503 are sequentially surrounded from the inside to the outside by a third insulating layer 403 and a fourth insulating layer 404.

[0189] In the phase-change memory chip provided in Example 2, the phase-change material layer 100 of the phase-change memory chip uses the improved phase-change material provided in the aforementioned embodiments of this disclosure, and an adhesive layer 200 is added between the phase-change material layer 100 and the barrier layer 300, thereby further improving the adhesion between the phase-change material layer 100 and the barrier layer 300.

[0190] In Example 3, Figure 11 shows a 1S1R type phase-change memory chip. The phase-change memory chip is placed on a substrate 004 and has a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. The plurality of memory subunits 001 are arranged in an array, the plurality of word lines 002 are arranged in sequential rows, and the plurality of bit lines 003 are arranged in sequential columns. Each memory subunit 001 is connected to the bit line 003 of the corresponding column via the upper electrode 501 of the memory subunit 001, and each memory subunit 001 is connected to the word line 002 of the corresponding row via the bottom electrode 502 of the memory subunit 001.

[0191] Each memory subunit 001 has a bottom electrode 502, a selector layer 600, an intermediate electrode 503, a barrier layer 300, a phase change material layer 100, an adhesive layer 200, another barrier layer 300, and an upper electrode 501, which are arranged sequentially from bottom to top in a stacked configuration. Adjacent memory subunits 001 are separated from each other by insulating layers. Specifically, in each memory subunit 001, the outer surfaces of the barrier layer 300, the phase change material layer 100, the adhesive layer 200, the barrier layer 300, and the upper electrode 501 are sequentially surrounded from the inside to the outside by a first insulating layer 401 and a second insulating layer 402, and the outer surfaces of the bottom electrode 502, the selector layer 600, and the intermediate electrode 503 are sequentially surrounded from the inside to the outside by a third insulating layer 403 and a fourth insulating layer 404.

[0192] In the phase-change memory chip provided in Example 3, the phase-change material layer 100 of the phase-change memory chip uses the improved phase-change material provided in the aforementioned embodiments of this disclosure, and furthermore, an adhesive layer 200 is added to the side of the phase-change material layer 100 closer to the upper electrode 501, thereby further improving the adhesion between the phase-change material layer 100 and the barrier layer 300.

[0193] In fact, in the phase-change memory chip provided in Example 3, the adhesive layer 200 may instead be added to the side of the phase-change material layer 100 closer to the selector layer 600, thereby increasing the bonding force between the phase-change material layer 100 and the barrier layer 300 closer to the selector layer 600.

[0194] As Example 4, Figure 12 shows a 1S1R type phase change memory chip. The phase change memory chip is placed on a substrate 004, and the 1S1R type phase change memory chip has a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. The plurality of memory subunits 001 are arranged in an array, the plurality of word lines 002 are arranged in sequential rows, and the plurality of bit lines 003 are arranged in sequential columns. Each memory subunit 001 is connected to the bit line 003 of the corresponding column via the upper electrode 501 of the memory subunit 001, and each memory subunit 001 is connected to the word line 002 of the corresponding row via the bottom electrode 502 of the memory subunit 001.

[0195] Each memory subunit 001 has a bottom electrode 502, a selector layer 600, an intermediate electrode 503, an adhesive layer 200, a phase change material layer 100, another adhesive layer 200, and an upper electrode 501, which are arranged sequentially from bottom to top in a stacked configuration. Adjacent memory subunits 001 are separated from each other by insulating layers. Specifically, in each memory subunit 001, the outer surfaces of the adhesive layer 200, the phase change material layer 100, the adhesive layer 200, and the upper electrode 501 are sequentially surrounded from the inside to the outside by a first insulating layer 401 and a second insulating layer 402, and the outer surfaces of the bottom electrode 502, the selector layer 600, and the intermediate electrode 503 are sequentially surrounded from the inside to the outside by a third insulating layer 403 and a fourth insulating layer 404.

[0196] In the phase-change memory chip provided in Example 4, the phase-change material layer 100 of the phase-change memory chip uses the improved phase-change material provided in the preceding embodiments of this disclosure, and furthermore, an adhesive layer 200 is added between the phase-change material layer 100 and the electrode layer to further improve the adhesion between the phase-change material layer 100 and the electrode layer.

[0197] In embodiments of this disclosure, several structural arrangements and preparation processes for 1S1R type phase-change memory chips are described as examples, with reference to one of the aforementioned phase-change materials.

[0198] As an example (1), such a 1S1R type phase change memory chip is provided and is placed on a silicon oxide substrate 004. The 1S1R type phase change memory chip has a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. As shown in Figure 9, each memory subunit 001 has a bottom electrode 502, a selector layer 600, an intermediate electrode 503, a barrier layer 300, a phase change material layer 100, a barrier layer 300, and an upper electrode 501, which are arranged sequentially from bottom to top in a stacked configuration, and adjacent memory subunits 001 are insulated from each other via an insulating layer. The plurality of memory subunits 001 are arranged in an array, the plurality of word lines 002 are arranged in sequential rows, and the plurality of bit lines 003 are arranged in sequential columns. Each storage subunit 001 is connected to the bit line 003 of the corresponding column via the upper electrode 501 of the storage subunit 001, and each storage subunit 001 is connected to the word line 002 of the corresponding row via the bottom electrode 502 of the storage subunit 001.

[0199] For example, the material of the word line 002 and the bit line 003 is all metallic tungsten W, the material of the upper electrode 501, the bottom electrode 502, and the intermediate electrode 503 is all carbon C, and the material of the barrier layer 300 is metallic tungsten W. The selector material used in the selector layer 600 is a currently available SiGeAsSe gate material. The phase change material of the phase change material layer 100 may be the phase change material in the first embodiment described above.

[0200] The preparation process for a 1S1R type phase-change memory chip is shown below.

[0201] As shown in Figure 14, a thin-film precursor for a phase-change memory chip is provided. The thin-film precursor comprises a substrate 004, a word line 002 layer, a bottom electrode 502, a selector layer 600, an intermediate electrode 503, a barrier layer 300, a phase-change material layer 100, another barrier layer 300, an upper electrode 501, and a mask layer 005, which are arranged sequentially from bottom to top in a stacked configuration. The mask layer 005 is mainly configured to protect the material layer beneath it, preventing the material layer beneath it from being affected in processes such as etching.

[0202] As shown in Figure 15, a first patterning process is performed on the thin film precursor to form a first groove 701. The first patterning process includes a photogravure process and an etching process. In the vertical direction (i.e., the Z-axis direction in Figure 15), the first groove 701 sequentially penetrates the mask layer 005, the upper electrode 501, the barrier layer 300, the phase change material layer 100, and the barrier layer 300 from top to bottom, exposing the intermediate electrode 503. In the first horizontal direction (i.e., the X-axis direction in Figure 15), multiple first grooves 701 are spaced apart to form multiple precursors for first memory units.

[0203] As shown in Figure 16, the first groove 701 is filled with an insulating material to form an insulating layer. This involves sequentially filling the first groove 701 with a first insulating material and a second insulating material, where the first insulating material forms a first insulating layer 401 surrounding the surface of the corresponding first memory unit precursor, and the second insulating material forms a second insulating layer 402 surrounding the surface of the first insulating layer 401. The material of the first insulating layer 401 is silicon nitride, and the material of the second insulating layer 402 is silicon dioxide. The first insulating layer 401 and the second insulating layer 402 can suppress the phase change material layer 100 from being affected by the subsequent etching process.

[0204] As shown in Figure 17, a second patterning process is carried out, and the first groove 701 extends downward in the vertical direction, forming a second groove 70. The second patterning process includes photoengraving and etching.

[0205] In the vertical direction, the second groove 702 sequentially penetrates the mask layer 005, the upper electrode 501, the barrier layer 300, the phase change material layer 100, the barrier layer 300, the intermediate electrode 503, the selector layer 600, the bottom electrode 502, and the word line 002 from top to bottom. In the first horizontal direction, a plurality of second grooves 702 are arranged at intervals to form a plurality of precursors for second memory units.

[0206] As shown in Figure 18, the step of filling the second groove 702 with an insulating material to form an insulating layer includes the step of sequentially filling the second groove 702 with a third insulating material and a fourth insulating material, wherein the third insulating material forms a third insulating layer 403 surrounding the surface of the corresponding second memory unit precursor, and the fourth insulating material forms a fourth insulating layer 404 surrounding the surface of the third insulating layer 403, resulting in an integrated third memory unit precursor. The material of the third insulating layer 403 is silicon nitride, and the material of the fourth insulating layer 404 is silicon dioxide. The third insulating layer 403 and the fourth insulating layer 404 perform insulating separation between different second memory unit precursors and can also mechanically support the second memory unit precursors.

[0207] As shown in Figure 19, the third memory unit precursor is polished to remove the mask layer 005 and expose the upper electrode 501. Next, bit lines 003 and a new mask layer 005 are sequentially formed on the surface of the upper electrode 501 to obtain an integrated fourth memory unit precursor. Figure 20 shows the cross-sectional structure of the fourth memory unit precursor along the second horizontal direction. The cross-section along the second horizontal direction is the cross-section indicated by the dashed line AB in Figure 19, and the second horizontal direction is the Y-axis direction in Figure 20, which is perpendicular to the X-axis direction mentioned above.

[0208] As shown in Figure 21, a third patterning process is performed on the fourth memory unit precursor to form a third groove 703. The third patterning process includes photoengraving and etching. In the vertical direction, the third groove 703 sequentially penetrates the mask layer 005, the bit line 003 layer, the upper electrode 501, the barrier layer 300, the phase change material layer 100, and the barrier layer 300 from top to bottom, exposing the intermediate electrode 503. In the second horizontal direction, a plurality of third grooves 703 are arranged at intervals to form a plurality of fifth memory unit precursors.

[0209] As shown in Figure 22, the step of filling the third groove 703 with insulating material to form an insulating layer includes the step of sequentially filling the third groove 703 with a first insulating material and a second insulating material, wherein the first insulating material forms a first insulating layer 401 surrounding the corresponding surface of the fifth memory unit precursor, and the second insulating material forms a second insulating layer 402 surrounding the surface of the first insulating layer 401, thereby obtaining an integrated sixth memory unit precursor.

[0210] Furthermore, as shown in Figure 22, the fourth patterning process is continued on the sixth storage unit precursor, causing the third groove 703 to extend downward in the vertical direction and forming the fourth groove. The fourth patterning process includes photoengraving and etching. In the vertical direction, the fourth groove sequentially penetrates the mask layer 005, the bit line 003 layer, the upper electrode 501, the barrier layer 300, the phase change material layer 100, the barrier layer 300, the intermediate electrode 503, the selector layer 600, and the bottom electrode 502 from top to bottom, exposing the word line 002. In the second horizontal direction, a plurality of fourth grooves are spaced apart to form a plurality of seventh storage unit precursors.

[0211] As shown in Figure 22, the step of filling the fourth groove with insulating material to form an insulating layer includes the step of sequentially filling the fourth groove with the third insulating material and the fourth insulating material, wherein the third insulating material forms the third insulating layer 403 and surrounds the corresponding surface of the seventh memory unit precursor, and the fourth insulating material forms the fourth insulating layer 404 and surrounds the surface of the third insulating layer 403, resulting in an integrated eighth memory unit precursor.

[0212] As shown in Figure 23, the eighth memory unit precursor is polished to remove the third insulating layer 403 and the fourth insulating layer 404 located above the mask layer 005 and bit line 003, thereby preparing the phase change memory chip provided in Embodiment 1.

[0213] In the phase-change memory chip provided in Embodiment 1, the phase-change material is improved, and the bonding strength between the phase-change material layer 100 and the barrier layer 300 is effectively improved, so that the yield of the phase-change memory chip does not decrease due to delamination or dropping between layers. Furthermore, the improved phase-change material still helps the phase-change memory chip to have advantages in characteristics such as a large read window, low latency, and long lifespan.

[0214] In this type of phase-change memory chip, the phase-change material is improved, effectively enhancing the bonding strength between the phase-change material layer 100 and the barrier layer 300, preventing a decrease in the yield of the phase-change memory chip due to delamination or drop between layers. Furthermore, the improved phase-change material contributes to the phase-change memory chip having advantages in characteristics such as a large read window, low latency, and long lifespan.

[0215] As Example (2), such a 1S1R type phase-change memory chip is provided. This type of 1S1R type phase-change memory chip includes a plurality of memory subunits 001, a plurality of word lines 002, and a plurality of bit lines 003. As shown in FIG. 10, each memory subunit 001 has a bottom electrode 502, a selector layer 600, an intermediate electrode 503, a barrier layer 300, an adhesion layer 200, a phase-change material layer 100, an adhesion layer 200, a barrier layer 300, and a top electrode 501, which are sequentially arranged from bottom to top in a stacked form, and adjacent memory subunits 001 are insulated from each other via an insulating layer. Compared with Example (1), the memory subunit 001 is additionally provided with the adhesion layer 200, while the arrangement of other layers remains the same. For example, the thickness of the adhesion layer 200 may be 2 nm, and the material of the adhesion layer 200 may be WN or InGeSbTe. WN may be W2N, WN, WN2, or a general formula of W x N 1-x may be any component satisfying the formula. Here, x is the atomic percentage, and 0 < x < 1. The InGeSbTe compound may be, for example, In3%-Ge2Sb2Te5, that is, the atomic percentage of In is 3%, and in the GeSbTe phase-change base material, the ratio of the atomic percentages of Ge, Sb, and Te is 2:2:5.

[0216] For the preparation process of the phase-change memory chip in this Example (2), reference is made to the above (1). The difference is that when the memory subunit 001 is formed, the adhesion layer 200 is formed at a specific position.

[0217] In the phase-change memory chip of this Example (2), the phase-change material is improved, and the adhesion layer 200 is additionally provided between the phase-change material layer 100 and the barrier layer 300, so that the adhesion between the phase-change material layer 100 and the barrier layer 300 is effectively improved. In addition, the total thickness of the two adhesion layers 200 may be 4 nm, which is only 1 / 10 of the thickness of the phase-change material layer 100, so the influence on the performance of the phase-change material layer 100 is small.

[0218] As example (3), such a 1S1R type phase-change memory chip is provided. For the structure and preparation process of the 1S1R type phase-change memory chip, refer to example (1). For the differences between the phase-change memory chip in example (3) and the phase-change memory chip in example (1), refer to Figure 12, in which the barrier layer 300 in Embodiment 1 is directly replaced by the adhesive layer 200, that is, the adhesive layer 200 is separately directly placed between the phase-change material layer 100 and the upper electrode 501, and between the phase-change material layer 100 and the intermediate electrode 503.

[0219] In the phase-change memory chip of this type (3), the phase-change material is improved, and an adhesive layer 200 is added between the phase-change material layer 100 and the electrode layer, thereby strengthening the adhesion between the phase-change material layer 100 and the electrode layer via the adhesive layer 200.

[0220] As an example (4), such a 1S1R type phase-change memory chip is provided. For the structure and preparation process of the 1S1R type phase-change memory chip, refer to Example (1). The difference between the phase-change memory chip in Example (4) and the phase-change memory chip in Example (1) is that the doping elements in the phase-change material used in the phase-change material layer 100 are limited to the elements Hf and In.

[0221] Example (5) provides such a 1S1R type phase-change memory chip. For the structure and preparation process of the 1S1R type phase-change memory chip, refer to Example (1). The difference between the phase-change memory chip in Example (5) and the phase-change memory chip in Example (1) is that the phase-change material of the phase-change material layer 100 may be the phase-change material of the second embodiment.

[0222] In the 1S1R type phase-change memory chip (5) in Example (5), characteristics such as delay, lifetime, high resistance, and low resistance of the phase-change memory chip are evaluated. The ratio of atomic percentages of atoms in the Ge-Sb-Te phase-change base material is Ge:Sb:Te = 1:4:7 (abbreviated as GST147). See Table 5 for the test results. Here, NA in Table 5 indicates that data is not available.

[0223] [Table 5]

[0224] Experiments have shown that when the atomic percentage of Sb in the Ge-Sb-Te phase-change base material is between 35% and 45%, the delay of the phase-change memory chip is less than 100 ns. When the atomic percentage of Sb in the Ge-Sb-Te phase-change base material exceeds 45%, the lifespan of the phase-change memory chip is shortened to some extent. When the atomic percentage of element Ge exceeds 15%, the delay of the phase-change memory chip is slowed down to some extent. When the atomic percentage of Ge is less than 6%, the adhesion strength of the phase-change material layer decreases.

[0225] As shown in Table 5, it is essential for phase-change memory chips to have a long lifespan if the sum of the atomic percentages of element Hf and element N is greater than 4%. When the atomic percentage of element Hf is 6.5% and the atomic percentage of element N is 5%, the sum of the atomic percentages of the two elements exceeds 10%, which greatly increases low resistance and makes the cycle procedure unstable.

[0226] As shown in Table 5, when the atomic percentage of element Hf is 8%, the high resistance of the phase change memory chip decreases, and the cycle becomes unstable. When the atomic percentage of element N is 8%, the low resistance of the phase change memory chip increases, but the low resistance during the cycle becomes unstable.

[0227] The phase-change memory chip provided in this embodiment of the Disclosure may replace solid-state drives (SSDs) based on the high-speed, high-density, and non-volatile properties of the phase-change memory chip. With further improvements in operating speed, the phase-change memory chip may be used in universal memory, having the functionality of both internal and external memory.

[0228] In another embodiment, one aspect of the present disclosure further provides a storage device. The storage device comprises a controller and one of the aforementioned phase-change storage chips. The controller is configured to store data in the phase-change storage chip. The controller reads / writes data stored in the storage device and interacts with and communicates with an external interface.

[0229] A storage device (also called memory) can be configured to store various types of data. This data may include contact data, phone book data, messages, photos, videos, or even instruction data.

[0230] The storage device in embodiments of this disclosure may be configured of various types, including, but is not limited to, internal memory, hard disks, magnetic disks, and optical disks.

[0231] In one embodiment of the present disclosure, an electronic device is further provided. The electronic device has a processor and the aforementioned storage device, wherein the processor is configured to store data generated by the electronic device in the storage device.

[0232] In some examples, electronic devices include, but are not limited to, computers, mobile phones, music players, digital broadcasting equipment, message transmission and reception devices, game controllers, medical devices, fitness equipment, portable digital assistants, and the like.

[0233] The foregoing description is merely intended to assist those skilled in the art in understanding the technical solutions of the present disclosure, and is not intended to limit the present disclosure. Any modifications, equivalent substitutions or improvements made without departing from the spirit and principles of the present disclosure shall fall within the protection scope of the present disclosure. Description of Reference Numerals

[0234] 001 Storage subunit 002 Word line 003 Bit line 004 Substrate 005 Mask layer 100 Phase change material layer 200 Adhesive layer 300 Barrier layer 400 Insulating layer 401 First insulating layer 402 Second insulating layer 403 Third insulating layer 404 Fourth insulating layer 501 Upper electrode 502 Lower electrode 503 Intermediate electrode 600 Selector layer 701 First groove 702 Second groove 703 Third groove

Claims

1. A phase change material, Ge-Sb-Te phase-change base material, The first doping element and the second doping element are doped into the aforementioned Ge-Sb-Te phase-change base material, Includes, The first doping element comprises the element Hf, and the atomic percentage of the first doping element in the phase change material is between 1.5% and 6.5%. A phase change material wherein the second doping element comprises at least one of the elements N, C, In, or Ga, and the atomic percentage of the second doping element in the phase change material is from 1.0% to 5%.

2. The phase change material further contains a third doping element, The phase change material according to claim 1, wherein the third doping element comprises at least one of the elements O, Si, B, Sn, Bi, Cd, Pb, Zr, Zn, Cr, Al, Sc, Y, Ta, Ti, Er, Lu, Ho, Tm, Dy, Tb, Ca, Nd, Pr, Yb, Ca, and Ce.

3. The chemical formula of the aforementioned Ge-Sb-Te phase-change base material is: (Get It) 1-a ) x (Sat) 2 yourself 3-b ) 1-x Here, x is the atomic percentage, 0 < x < 1, a and b are parameters relating to the atomic weight ratio, 0 < a ≤ 1 and 0 < b ≤ 3, and a = 1 and b = 3 do not coexist, or (Get It) 1-c ) x (Sat) y yourself 1-d ) 1-x The phase change material according to claim 1 or 2, wherein x is an atomic percentage, 0 < x < 1, and y, c, and d are parameters relating to the atomic weight ratio, y ≥ 2, 0 < c ≤ 1, 0 < d ≤ 1, and c = 1 and d = 1 are incompatible.

4. A phase change material, Ge-Sb-Te phase-change base material, The first doping element and the second doping element are doped into the aforementioned Ge-Sb-Te phase-change base material, Includes, The first doping element comprises the element Hf, and the atomic percentage of the first doping element in the phase change material is between 1.5% and 7%. The second doping element comprises at least one of the elements N, C, In, and Ga, and the atomic percentage of the second doping element in the phase change material is between 1.0% and 7%. A phase change material in which the sum of the atomic percentages of the first doping element and the atomic percentages of the second doping element is greater than 4% and less than 10%.

5. The phase change material further contains a third doping element, The phase change material according to claim 4, wherein the third doping element comprises at least one of the elements O, Si, B, Sn, Bi, Cd, Pb, Zr, Zn, Cr, Al, Sc, Y, Ta, Ti, Er, Lu, Ho, Tm, Dy, Tb, Ca, Nd, Pr, Yb, Ca, and Ce.

6. The chemical formula of the aforementioned Ge-Sb-Te phase-change base material is: (Get It) 1-a ) x (Sat) 2 yourself 3-b ) 1-x Here, x is the atomic percentage, 0 < x < 1, a and b are parameters relating to the atomic weight ratio, 0 < a ≤ 1 and 0 < b ≤ 3, and a = 1 and b = 3 do not coexist, or (Get It) 1-c ) x (Sat) y yourself 1-d ) 1-x The phase change material according to claim 4 or 5, wherein x is an atomic percentage, 0 < x < 1, and y, c, and d are parameters relating to the atomic weight ratio, y ≥ 2, 0 < c ≤ 1, 0 < d ≤ 1, and c = 1 and d = 1 are incompatible.

7. The chemical formula of the aforementioned Ge-Sb-Te phase-change base material is: (Get It) 1-a ) x (Sat) 2 yourself 3-b ) 1-x And here, 0.2 < x ≤ 0.4, or (Get It) 1-c ) x (Sat) y yourself 1-d ) 1-x The phase change material according to claim 6, wherein 0.2 < x ≤ 0.

4.

8. It is a phase-change memory chip, It has multiple phase change memory units, and each phase change memory unit has a phase change material layer. The phase change material layer is prepared using the phase change material described in any one of claims 1 to 3, or A phase-change memory chip wherein the phase-change material layer is prepared using the phase-change material described in any one of claims 4 to 7.

9. The phase change memory unit further comprises an adhesive layer, which is arranged in a laminated configuration on at least one surface of the phase change material layer. The phase change memory chip according to claim 8, wherein the adhesive layer is configured to enhance the adhesive strength between the phase change material layer and the adjacent functional layer.

10. The adhesive layer material used in the adhesive layer comprises at least one nitride of the target element and a carbide of the target element. The phase change memory chip according to claim 9, wherein the target element is selected from at least one of the elements W, Ti, Ge, Ta, Hf, In, Ga, Al, Cu, Co, and Mo.

11. The adhesive layer raw material used in the adhesive layer comprises a Ge-Sb-Te phase change material doped with a fourth doping element, and unlike the phase change material, The phase change memory chip according to claim 9, wherein the fourth doping element is selected from at least one of the elements Hf, N, C, In, and Ga, and the atomic percentage of the fourth doping element in the adhesive layer material is 0.01 to 20%.

12. The phase change memory unit further has a barrier layer, The phase change memory chip according to any one of claims 9 to 11, wherein the adhesive layer is disposed between the phase change material layer and the barrier layer and is configured to enhance the adhesive strength between the phase change material layer and the barrier layer.

13. The phase change memory chip according to claim 12, wherein the barrier layer material used in the barrier layer comprises at least one of single-element materials of element W, element Ti, element Ge, element Ta, element Hf, element In, element Ga, element Al, element Cu, element Co, and element Mo, nitrides, and carbides.

14. The phase change memory unit further has an electrode layer, The phase change memory chip according to any one of claims 9 to 11, wherein the adhesive layer is disposed between the phase change material layer and the electrode layer and is configured to increase the adhesive strength between the phase change material layer and the electrode layer.

15. The phase-change memory chip further has a plurality of selector units, and the selector units and the phase-change memory unit are arranged in series. The phase change memory chip according to any one of claims 8 to 14, wherein the selector unit has a selector layer, and the selector material used in the selector layer has at least one of an S-series selector material, a Se-series selector material, and a Te-series selector material.

16. The selector material further comprises a fifth doping element, The phase change memory chip according to claim 15, wherein the fifth doping element is selected from at least one of the elements B, Al, Ga, In, C, Si, Ge, Sn, N, P, As, Sb, Bi, O, Au, Hf, Pd, Cu, Co, Ag, Pt, Sc, Ti, and Ta.

17. It is a memory device, The device comprises a controller and at least one phase-change memory chip as described in any one of claims 8 to 16, The controller is a memory device configured to store data in the phase-change memory chip.

18. An electronic device, The system comprises a processor and the storage device described in claim 17, The processor is configured to store data generated by the electronic device in the memory device.